Pocket Music Theory: The Development of Augmented Reality (AR) Basic Music Theory Learning Mobile Application - Sim, Shin Ying; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2022)
Augmented reality (AR) technology is widely used for educational purposes including music theory learning. However, in The Sea Music Studio, the main music theory education material is still paper-based which causes issues like an inconvenience to carry, easy getting dirty and damage, especially for children. Hence, the basic music theory learning mobile application, namely Pocket Music Theory is developed on the Android platform to overcome the problems and allow the user to carry out music theory learning at any time anywhere. Multimedia Mobile Content Development (MMCD) is used as the methodology for developing the application. This application is expected to allow the user to scan and learn music theory with marker-based AR and provide quiz and summary modules for practice and revision. Thus, children could learn music theory in a fun environment and the development of mobile learning applications for higher music theory grades could be carried out in future.